The maize brown midrib2 (bm2) gene encodes a methylenetetrahydrofolate reductase that contributes to lignin accumulation - Tang, Ho Man; Liu, Sanzhen; Hill-Skinner, Sarah; Wu, Wei; Reed, Danielle; Yeh, Cheng-Ting; Nettleton, Dan; Schnable, Patrick S. (My University, 2013)
The midribs of maize brown midrib (bm) mutants exhibit a reddish-brown color associated with reductions in lignin concentration and alterations in lignin composition. Here, we report the mapping, cloning, and functional and biochemical analyses of the bm2 gene. The bm2 gene was mapped to a small region of chromosome 1 that contains a putative methylenetetrahydrofolate reductase (MTHFR) gene, which is down-regulated in bm2 mutant plants. Analyses of multiple Mu-induced bm2-Mu mutant alleles confirmed that this constitutively expressed gene is bm2. Yeast complementation experiments and a previously published biochemical characterization show that the bm2 gene encodes a functional MTHFR. Quantitative RT-PCR analyses demonstrated that the bm2 mutants accumulate substantially reduced levels of bm2 transcript. Alteration of MTHFR function is expected to influence accumulation of the methyl donor S-adenosyl-l-methionine (SAM). Because SAM is consumed by two methyltransferases in the lignin pathway (Ye et al., 1994), the finding that bm2 encodes a functional MTHFR is consistent with its lignin phenotype. Consistent with this functional assignment of bm2, the expression patterns of genes in a variety of SAM-dependent or -related pathways, including lignin biosynthesis, are altered in the bm2 mutant. Biochemical assays confirmed that bm2 mutants accumulate reduced levels of lignin with altered composition compared to wild-type. Hence, this study demonstrates a role for MTHFR in lignin biosynthesis.
Citation: Tang, H., . . . & Schnable, P. (2013). The maize brown midrib2 (bm2) gene encodes a methylenetetrahydrofolate reductase that contributes to lignin accumulation. The Plant Journal, 77(3), 380-392. https://doi.org/10.1111/tpj.12394
Keywords: Zea mays; Brown midrib; Lignin; Methylenetetrahydrofolate; S-adenosyl-L-methionine